Footprints discovering the Holocaust through historical artefacts - Salmons, Paul; Reetz, Cornelia (The Holocaust Centre [u.a, 2010)
This educational video was created for the Footprints for Hope project, a new initiative from the Holocaust and the United Nations Outreach Programme designed to involve students aged 13 years and older in the study of the Holocaust. This film is accompanied by a lesson plan and PowerPoint presentation titles “Ordinary Things? Discovering the Holocaust through Historical Artefacts”. The activity centres around one of the most painful graphic images from the Holocaust, the shoes of the victims who perished in Nazi death camps. Following the classroom lesson, students will draw inspiration for a more hopeful future by creating colourful art out of used footwear. The aim of this activity is to further the students’ understanding of the Holocaust and encourage respect for human rights and the dignity and worth of every person.